PENGARUH KESULITAN KEUANGAN, RISIKO LITIGASI DAN TINGKAT UTANG TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN SUB SEKTOR KONSTRUKSI BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2024 - Purba, Rizka Amalia; Pane, Aditya Amanda (Investama : Jurnal Ekonomi dan Bisnis, 2025)
Accounting conservatism is an accounting principle that emphasizes prudence in financial reporting, where income and assets are recognized at lower values, while expenses and liabilities are recognized at higher values to reduce the risk of overstatement. In the context of construction companies listed on the Indonesia Stock Exchange (IDX), the level of accounting conservatism can be influenced by several factors, such as financial distress, litigation risk, and debt level. The data in this study were obtained from the annual financial statements of construction and building companies accessed through the official IDX website for the period 2020 to 2024. This study uses secondary data with a multiple linear regression analysis method using SPSS version 27. Based on the research results, it was found that: (1) The statistical test results show that financial distress has a positive and significant partial effect on accounting conservatism. This indicates that the higher the level of financial distress a company experiences, the more likely management is to apply accounting conservatism to reduce the risk of asymmetric information and to provide a prudence signal to investors. (2) The statistical test results show that litigation risk has no significant partial effect on accounting conservatism. This condition reflects that even though the company faces potential legal lawsuits, management does not directly consider this factor as a basis for determining accounting conservatism policies. (3) The statistical test results show that the debt level has no significant partial effect on accounting conservatism. This indicates that the leverage level of construction companies does not exert sufficient pressure on management to tighten conservative accounting policies. (4) Simultaneously, financial distress, litigation risk, and debt level contribute 73.1% to the variation in accounting conservatism, while the remaining 26.9% is influenced by other factors outside this research model, such as audit quality, ownership structure, and company size. The results of this study are in line with agency theory, which explains that conflicts of interest between management and shareholders encourage the application of conservatism to reduce the potential for information manipulation. In addition, these findings also support signaling theory, where management uses accounting conservatism as a signal of prudence and transparency in the company’s financial condition to investors.